2014
DOI: 10.5430/ijdi.v2n1p1
|View full text |Cite
|
Sign up to set email alerts
|

The role of PET scans in the management of Cholangiocarcinoma and Gallbladder Cancer: A systematic review for surgeons

Abstract: Introduction: Radical surgical resection is the only potentially curative therapy for cancers arising in biliary epithelia (gallbladder cancer and cholangiocarcinoma). Accurate radiological staging is crucial and the role of positron emission tomography-CT (PET-CT) scanning in this regard is undefined. Methods:A systematic review of the literature was carried out to define the accuracy of PET-CT in patients with cholangiocarcinoma or gallbladder cancer in defining metastatic disease in portal, and extra-portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A systematic review has also shown that PET‐CT has a definitive role for detecting both intra and extra‐abdominal metastases predominantly in patients with doubtful standard cross‐sectional imaging findings but has no role in evaluation of small hepatic satellite lesions …”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has also shown that PET‐CT has a definitive role for detecting both intra and extra‐abdominal metastases predominantly in patients with doubtful standard cross‐sectional imaging findings but has no role in evaluation of small hepatic satellite lesions …”
Section: Discussionmentioning
confidence: 99%